Epidemiology of tumors of the spinal cord and spine in Ukraine in 2000-2019 - Pedachenko, Eugene G.; Slynko, Ievgenii I.; Nekhlopochyn, Oleksii S.; Nikiforova, Anna N.; Botev, Viacheslav S.; Yovenko, Tetyana A. (Ukrainian Neurosurgical Journal, 2021)
Objective. To determine the dynamics and state of neurosurgical care for tumors of the spinal cord and spine (TSCS) in Ukraine. Materials and methods. The work is based on the analysis of hospitalizations and surgical treatment of patients with TSCS in neurosurgical departments of Ukraine in 2000-2019. Results. In 2019, 1,325 patients with TSCS were hospitalized in neurosurgical departments of Ukraine, which is 2,3 times more than in 2000 (567), per 1 million population - almost 3 times (34,7 vs. 11, 6 ). Over 20 years, the number of operated patients increased 2,8 times (from 385 to 1079), per 1 million population - 3,6 times (from 7,9 to 28,3), there was an increase in surgical activity by 20% (from 67,9 to 81,4%), a decrease in the general and postoperative mortality - twice (from 2,6 to 1,2% and from 2,6 to 1,3% respectively). Patients with TSCS account for 1,5% of all patients hospitalized in neurosurgical departments of Ukraine, 12,8% of all CNS neoplasms and 5,2% of all spinal pathology. Vertebral tumors account for 42,64% of all TSCS and extramedullary tumors have an incidence rate similar to vertebral tumors (42,64%), intramedullary tumors account for 14,72%. In 2019, 74.4% more patients with extramedullary tumors were hospitalized than in 2000 (565 and 324 respectively), and 84.5% more were operated on (463 and 251 respectively). The rate of increase is even higher per 1 million population. In 2019, there were 14.8 hospitalizations per 1 million population for extramedullary tumors, which is 2.2 times greater than in 2000 (6,6 hospitalizations), and 12,1 operations, which is 2,4 times greater than in 2000 (5,1 operations). In 2019, patients with intramedullary tumors were hospitalized 2,2 times more than in 2000. (195 and 89 respectively), were operated 2,5 times more (151 and 61 respectively). The rate of increase is even 4higher per 1 million population. In 2019, there were 5,1 hospitalizations for intramedullary tumors per 1 million population, which is 2,8 times greater than in 2000 (1,8 hospitalizations), and 4,0 operations, which is 3,2 times greater than in 2000 (1,2 operations). In 2019, patients with vertebral tumors were hospitalized 3.7 times more than in 2000 (565 and 154 respectively), were operated 6,4 times more (465 and 73 respectively). The rate of increase is even higher per 1 million population. In 2019, there were 14,8 hospitalizations per 1 million population for vertebral tumors, which is 4,7 greater than in 2000 (3,1 hospitalizations), and 12,2 surgeries, which is 8,2 greater than in 2000 (1,5 operations). Сonclusions. The introduction of modern neuroimaging methods and advanced treatment methods into clinical practice has contributed to an increase in the number of hospitalizations and surgical interventions in TSCS.